Yes, the medium matters: How Facebook and Twitter boost populism in Europe - Piergiuseppe Fortunato; Marco Pecoraro (University of Neuchâtel, Institute of Economic Research (IRENE), 2020)
This paper examines how socio-economic characteristics, changes in the technology of political communication and their interactions affect the sentiments of the electorate and favor the spread of populist ideas in Europe. Using both European-wide and national surveys we find a significant association between exposure to online political activity and diffusion of populist ideas such as Euroscepticism only among less educated and economically vulnerable individuals. We also show that it is not the use of the internet per se that matters but the specific use of social networks for political activity.
Keywords: D72; N34; L82; L86; Z13; 330; Populism; Euroscepticism; Internet; Social Networks; Education